IMPROVING STUDENTS’ ABILITY IN WRITING SHORT FUNCIONAL TEXT CONGRATULATION AND COMPLIMENTING USING PICTURE SEQUENCES - Januar Tri Sejati; Mohamad Ikhsan Aditia (PROJECT (Professional Journal of English Education), 2019)
This study was aimed to improve student’s ability in writing short funcional text congratulation and complimenting using picture sequences at X MA Nurulhidayah Batujajar in the academic year of 2018/2019 as the subject of the study consists 32 students. This study was conducted for two months.The CAR was done based on Kurt Lewins’ design. The writer did two cycles which each cycle consists with planning, acting, observing, and reflecting. For data were gathered through qualitative and quantitative. The qualitative data were gained by analyzing the interview and observation result, while quantitative data were obtained from the students’ writing score of pretest and posttest.The finding of this study showed that there was improvement on the student’s ability in writing short funcional text congratulation and complimenting using picture sequences. It can be seen from the mean score of pretest was 56.75. Then, the mean score of posttest cycle 1 was 66.37 and the mean score of posttest cycle 2 was 72.62. so the criteria of success was achieved. from the result of questionnaire, it showed that there was improvement of positive responses in the teaching-learning process of writing short funcional textcongratulation and complimenting. Related to the result of observation and interview, it can be concluded that the students’ ability in writing short funcional texcongratulation and complimenting using picture sequences improved and the students’ were motivated in the teaching-learning process.